Stump Appendicitis: An Uncompleted Surgery, a Rare but Important Entity with Potential Problems - J. A. A. Awe; A. M. Soliman; R. W. Gourdie (Case Reports in Surgery)
Appendicectomy for appendicitis is one of the commonest surgical procedures performed worldwide. The residual appendiceal stump left after an initial appendectomy risks the development of stump appendicitis. Stump appendicitis is a real recognized entity but not often considered when evaluating patients with right lower quadrant abdominal pain, especially those with past history of appendectomy. It remains a clinical challenge with the result that its diagnosis and effective treatment are often delayed with possible attendant morbidity or mortality. Stump appendicitis results from obstruction of the lumen of the remaining appendix stump, usually by a faecolith. This increases intraluminal pressure, impairing venous drainage and allowing subsequent bacterial infection. We present the case of a twenty-five (25)-year-old female who underwent laparoscopic appendicectomy and presented four and half (4(1/2)) months later with fever, right lower quadrant abdominal pain, and tenderness associated with repeated vomiting. Exploratory laparotomy was carried out after clinical and imaging studies which revealed big inflammatory mass with abscess at the right iliac fossa and recurrent appendicitis of the appendiceal stump. Surgical treatment is easy but recognition of this important entity but potentially dangerous condition should always be borne in mind in order to avoid delay in its diagnosis and treatment.